If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4cos(3x) = 1 Remove parenthesis around (3x) 4cos * 3x = 1 Reorder the terms for easier multiplication: 4 * 3cos * x = 1 Multiply 4 * 3 12cos * x = 1 Multiply cos * x 12cosx = 1 Solving 12cosx = 1 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Divide each side by '12osx'. c = 0.08333333333o-1s-1x-1 Simplifying c = 0.08333333333o-1s-1x-1
| 5x+2y=18fory | | 7cos(t)-5sin(2t)=0 | | 3(5-2x)(3+4x)=0 | | 48+7x=22 | | 8-m=22-3m | | d+18=8-3d | | d+18=18-3D | | a*4+2=14 | | 6x+20=62 | | 18(2x+7)=162 | | at7/3=a-3/5 | | log(x)=3.77 | | 3x-10=x-4 | | 5y-16=y+3 | | 5x-3-7x+4=-4x+6+7x+5 | | 2(3n-1)-4(3-2n)=14 | | 26-4x=5-7x | | 10000x^2+250x+1=0 | | 255+10*x^4=1255 | | x^4-4x^3-6x^2+9=0 | | 3x^3-5x^2-3=0 | | 6x-5=15-77 | | 3x(7x-1)=0 | | -8+7x+7x=-106 | | 6-8+7x+7x=-106 | | (3x+4)=o | | 2(x+2)=-2x+36 | | -47=3(5x+2)-8 | | x^3+y^3+8y-8x=0 | | 5-3g+6(2g-7)= | | x^2-x+y^2+2y=0 | | 2(x-2)+2(x+5)=2x+2(2x-1) |